2021
DOI: 10.1016/j.synbio.2021.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharide phosphorylases: Structure, catalytic mechanisms and directed evolution

Abstract: Disaccharide phosphorylases (DSPs) are carbohydrate-active enzymes with outstanding potential for the biocatalytic conversion of common table sugar into products with attractive properties. They are modular enzymes that form active homo-oligomers. From a mechanistic as well as a structural point of view, they are similar to glycoside hydrolases or glycosyltransferases. As the majority of DSPs show strict stereo- and regiospecificities, these enzymes were used to synthesize specific disaccharides. Currently, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Similar to glycoside hydrolases or glycosyltransferases, disaccharide phosphorylases (DSPs) are modular enzymes which produce active homo-oligomers with attractive properties, especially specific disaccharides. Sun and You summarize the properties and classifications of known DSPs and their applications for glycoside products [ 16 ]. Protein chemical modifications, such as unnatural amino acid incorporation by genetic coding expansion, enzymatic tailoring reactions and recognition-driven transformations, are imperative means for clarifying chemical and biological functions of enzymes and proteins.…”
Section: Enzymes and Proteinsmentioning
confidence: 99%
“…Similar to glycoside hydrolases or glycosyltransferases, disaccharide phosphorylases (DSPs) are modular enzymes which produce active homo-oligomers with attractive properties, especially specific disaccharides. Sun and You summarize the properties and classifications of known DSPs and their applications for glycoside products [ 16 ]. Protein chemical modifications, such as unnatural amino acid incorporation by genetic coding expansion, enzymatic tailoring reactions and recognition-driven transformations, are imperative means for clarifying chemical and biological functions of enzymes and proteins.…”
Section: Enzymes and Proteinsmentioning
confidence: 99%
“…Although the synthetic potential of β-1,3-D-glucan phosphorylases towards long oligosaccharides remains underexplored compared to β-1,4-D-glucan phosphorylases, the biocatalytic synthesis of d -laminaribiose has been investigated in combination with other enzymes aiming at the industrial scale production in view of its biological importance and commercial applications. Many studies have demonstrated the outstanding in vitro activity of SCP as part of multi-enzyme synthetic processes in which downstream reactions catalysed by other phosphorylases use α-D-Glc-1P generated in situ through the conversion of expedient feedstock, thus leading to highly valuable sugars as already exemplified herein for β-1,4-linkage and broadly covered in recent reviews [ 23 , 133 , 134 ]. In this aspect, d -laminaribiose was produced from sucrose and D-Glc in a one-pot reaction containing individually immobilised SCP and E. gracilis extract with enriched LBP activity ( Fig.…”
Section: Glycoside Phosphorylasesmentioning
confidence: 99%
“…This reaction is reversible [15]. According to the stereochemical results of the enzyme-catalyzed reaction product, phosphorylase can be divided into retention type and inversion type [16]. The glycoside phosphorylases reported so far are mainly classified into the glycoside hydrolase family (GH family) in the Carbohydrate-Active Enzymes database (http:// www.…”
Section: Introductionmentioning
confidence: 99%